Peranan Wisata Setigi (Selo Tirto Giri) dalam Peningkatkan Pendapatan Asli Desa (Pades) Di Desa Sekapuk Kecamatan Ujung Pangkah Kabupaten Gresik - Pramudiana, Ika Devy; Rafiatma, Zuhdi Ahmadi; Kamariyah, Sri; Sholichah, Nihayatus (Prodi Sosiologi Agama, 2022)
Tourism is the most important sector in economic development and development. Tourism in Indonesia as a supporting factor for the economy has bright prospects. One of the local governments that is quite successful in exploring and developing the tourism potential of this new village is Gresik Regency through Sekapuk Village which has Setigi tourism. Setigi tourism is part of the policy product carried out by the Sekapuk Village government, the mechanism for establishing Setigi tourism is part of the results of the Sekapuk Village deliberations. In recent years, Gresik Regency has tended to focus on tourism development in its area as an alternative to the mining industry. The purpose of this research is to find out the role of Setigi tourism in increasing village original income in Sekapuk village, Panceng district, Gresik Regency, this needs to be done because the community is a very important element to support the successful development of an area. This study used qualitative research methods. The results of this study are showing the success of Setigi tourism in increasing Regional Original Income and being able to bring in new economic sources other than being farm laborers. It is known that there has been an increase in the APBdes in Sekapuk Village in the last 4 years, namely an increase in PADes from 2019 to 2021, an increase of 100% over 2,380,014,655 in 2019 to 9,590,701,000,00 in 2021, while there is an increase in the aspect of MSME movement, one of which is the involvement of MSME residents who always sell in the area. tourism, as well as employing local residents in tourism Setigi.